Conflict, cooperation, and collective action: Land use, water rights, and water scarcity in Manupali watershed, Southern Philippines - Piñon, Caroline; Catacutan, Delia; Leimona, Beria; Abasolo, Emma; van-Noordwijk, Meine; Tiongco, Lydia (International Food Policy Research Institute, 2012)
Sustaining the environmental, social, and economic development in Manupali watershed in southern Philippines is highly dependent on equitable allocation of water use rights and judicious utilization of water as a scarce resource. There are many stakeholders and water users: smallholder farmers, indigenous people, multi-national companies, the local government, the National Irrigation Administration, and the National Power Corporation (Pulangui IV). As demand for water outstrips supply, conflict arises between different user groups over who can use water and how much each one can use. This paper reports initial results of an ongoing study that examines water rights and land use change to better negotiate for greater investment in watershed management. A key issue in Manupali is overall water scarcity, compounded by conflicting water rights of different users. To avoid hostile confrontation between different user groups and to manage competition of water use, some user groups have instituted voluntary agreements for water rights sharing. Viewed in terms of cooperation and collective action, these voluntary agreements facilitate conflict management of a disputed resource, but the fairness and equity of such agreements are in question, as the cooperating user groups extract benefits from non-cooperators who may have incurred the costs of protecting the upper watershed to maintain water supply. Supported by watershed hydrological data on water balance and its land use patterns, this paper argues that water rights sharing through voluntary agreements alone can only mediate short-term conflict but will not solve water scarcity in the longer term. The problems of water scarcity, allocation, and land use, require collective action beyond the current level if equitable distribution of benefits, sharing of responsibilities, and co-investments in watershed management are the goals.